电缆线路设计的统计编辑方法、系统、存储介质及设备 (2022)
本发明涉及电缆工程数字技术领域，提供电缆线路设计的统计编辑方法、系统、存储介质及设备，其中所述电缆线路设计的统计编辑方法包括：根据电缆线路设计的工程图纸生成统计表格，所述工程图纸和所述统计表格分别具有多项属性；关联所述工程图纸和所述统计表格，使其中任一者的属性改动时自动同步至另一者；将所述工程图纸和统计表格设于同一显示界面，二者处于显示界面的部分可进行调整；关联所述工程图纸和统计表格的显示部分，其中任一者的显示部分发生变化，另一者的显示部分随之发生变化；所述显示部分为处于显示界面的部分。本发明能有效提高电缆线路中的设计及统计的效率和准确率。 The invention relates to the technical field of cable engineering digital, and provides a statistical editing method and system for cable line design, a storage medium and equipment, and the method comprises the steps: generating a statistical table according to an engineering drawing of the cable line design, the engineering drawing and the statistical table respectively having a plurality of attributes; associating the engineering drawing with the statistical table, and automatically synchronizing the attribute of any one of the engineering drawing and the statistical table to the other one when the attribute is changed; setting the engineering drawing and the statistical table on the same display interface, wherein the parts of the engin